Chemical Composition of Spent Pleurotus eryngii Mushroom Substrate and Its Reuse for Volvariella volvacea Production - Sun 1, Xian; Xu 1, Hui; Liang 1, Huibing; Li 1, Pei; Qiao1, Dairong; Cao 1, Yi; Zhang 2, Liang (Asian Journal of Chemistry, 2014)
The nutrient compositions, physical components and metal contents of spent Pleurotus eryngii mushroom substrate (SMS) and traditional wheat straw substrate (WS) were analyzed. The result show that SMS can be used for the cultivation of V. volvacea. The effects of compost of SMS, additive of WS, substrate moisture content and initials pH on yield, bioconversion efficiency, spawn growth and nutrition of fruit body were investigated. The cultivation result show that composted SMS was successfully used as basic substrate for V. volvacea production with adjusted the initial pH of 8 and 70 % of moisture content. In laboratory and large scale cultivation experiments, the average biological efficiency of the cultivated on SMS were 26.12 and 27.42 %, respectively, considerably higher than the corresponding values on traditional WS controls of 17.92 and 20.17 %. The proximate composition, amino acids, trace elements of the fruit body cultivation between SMS and WS media were analyzed. The result indicated that V. volvacea cultivate on SMS had a higher nutritional value than those grown on WS.